Evaluasi Pelatihan Dan Pengembangan Sumber Daya Manusia Pada Disiplin Kerja Dan Kinerja Karyawan - Rahman, Reza Winanda; Nurbiyati, Titik (208-7721)
Training and development of human resources is indispensable organization to improve work discipline and performance. The purpose of this study was to analyze the influence of training and human resource development in the discipline of work and performance, discipline of work on performance as well as to determine the training and development affect performance directly or indirectly through labor discipline. Respondents in this study were 80 employees PT.Pertamina Upstream Energy West Madura Offshore. Methods of data collection using questionnaires and analysis tools used descriptive, regression and path analysis. Results of this study showed that the training and development has an effect on the work and performance discipline, work discipline affect performance, and training directly affects the performance while the effect on the performance through the development of labor discipline.